Acute metabolic acidosis enhances circulating parathyroid hormone, which contributes to the renal response against acidosis in the rat. - Bichara, M (1990)
Acute PTH administration enhances final urine acidification in the rat. HCl was infused during 3 h in rats to determine the parathyroid and renal responses to acute metabolic acidosis. Serum immunoreactive PTH (iPTH) concentration significantly increased and nephrogenous adenosine 3H,5H-cyclic monophosphate tended to increase during HCl loading in intact and adrenalectomized (ADX) rats despite significant increments in plasma ionized calcium. Strong linear relationships existed between serum iPTH concentration and arterial bicarbonate or proton concentration (P less than 0.0001). Serum iPth concentration and NcAMP remained stable in intact time-control rats and decreased in CaCl2-infused, nonacidotic animals. Urinary acidification was markedly reduced in parathyroidectomized (PTX) as compared with intact rats during both basal and acidosis states; human PTH-(1-34) infusion in PTX rats restored in a dose-dependent manner the ability of the kidney to acidify the urine and excrete net acid. Acidosis-induced increase in urinary net acid excretion was observed in intact, PTX, and ADX, but not in ADX-thyroparathyroidectomized rats. We conclude that (a) acute metabolic acidosis enhances circulating PTH activity, and (b) PTH markedly contributes to the renal response against acute metabolic acidosis by enhancing urinary acidification.